Pengaruh Pendidikan Dan Investasi Terhadap Pengangguran Di Jawa - Ameilia Karisma; Waspodo Tjipto Subroto; Hariyati Hariyati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
Indonesia is one of the most densely populated countries in the world so that this country has a population of productive age. However, Java Island has several provinces with varying unemployment rates. This study uses secondary data obtained from the Central Statistics Agency and via the internet to complete the data. The analytical method used in this research is multiple linear regression with the help of Eviews software. The results showed that the education and investment variables consisting of foreign investment did not have a significant effect on the unemployment variable and investment which consisted of domestic investment had a significant effect on the unemployment variable through the t test. The coefficient of determination (R2) is 0.3686, which means that 36.9 percent of the variation in unemployment in Java can be explained by variations in the 3 independent variables, namely economic growth and unemployment, while it is explained by other variables not mentioned in the research model. Keywords: Education , Investment, Unemployment Rate.